Analisis SWOT pemetaan media tentang halal lifestyle di Indonesia dengan NVivo: Studi literatur review - Bagaskara, Doni Yusuf; Rohmadi, Rohmadi (Journal of Halal Industry Studies, 2024)
This research aims to determine a SWOT analysis regarding Halal Lifestyle Consumption Behavior in Indonesia using the NVivo approach. This research uses qualitative methodology with the NVivo approach and literature review. "Data analysis techniques include (1) mapping the number of news article codes based on qualitative analysis using Nvivo 14 software regarding "Halal Lifestyle," (2) mapping visualization results with hierarchical diagrams and testing the correlation between media articles using Nvivo 14 software; (3) mapping research topics with the World Cloud or a collection of words that are often discussed in media articles; and (4) testing the significant value between media articles to determine the size of the correlation around the topic "Halal Lifestyle." This research shows that the words often appear in media articles are topics regarding Halal, Indonesia, products, and industry. Apart from that, the topics often discussed by media articles regarding Halal Lifestyle are threats and opportunities. Meanwhile, topics rarely discussed by media articles regarding Halal lifestyle are weaknesses and opportunities.